ANALISIS PENDAPATAN PETERNAKAN AYAM BURAS YANG DI PELIHARA SECARA EXTENSIF DI KECAMATAN DIMEMBE - Yarbo, Rahmat; Wantasen, E; Salendu, A H.S; Waleleng, P O.V (Universitas Sam Ratulangi, 2020)
ABSTRACTINCOME ANALYSIS OF NATIVE CHICKEN FARMING RAISED EXTENSIVELY IN DIMEMBE SUBDISTRICT. The goal of this research were to investigate the income on the business of domestic poultry that is maintained extensively and to determine the factors that influence it. The study was conducted by using survey and interview methods based on a list of questions toward 80 respondents of native chicken farmers in Dimembe Sub District. Data analysis were descriptive and quantitative analysis. Quantitative analysis was done by using multiple regression techniques of the Cobb-Douglass model. The results showed that the average net income from selling free-range chickens, which is Rp. 2.780.471,875 /year / breeder. The results of the regression analysis showed that altogether the independent variables influenced the income of farmers as much as 73.1%. Partially the independent variables that significantly influence farmers 'income (P<0,05) were labor costs and farmers' perceptions while feed costs drug and vitamin costs and the cage cost were not significantly effect on breeder’s income from native chicken farming (P> 0.05) Production costs of a locally-grown free-range chicken farm are mostly used to buy feed.